ANALISIS KINERJA KEUANGAN SERTA KEMAMPUAN KEUANGAN PEMERINTAH DAERAH DALAM PELAKSANAAN OTONOMI DAERAH KABUPATEN BUTON UTARA - Ningsih, Sri Ayu (Pusat Studi Ekonomi Publikasi Ilmiah dan Pengembangan SDM Azramedia indonesia, 2022)
Regional autonomy is a first step towards national economic development more powerful high growth by providing a better life for the community area. In carrying autonomous region, the regional government to run the government are required for effective, efficient and able to push the role of communities and improving equity and justice by developing the entire potential of each region. This study aims to determine the financial capacity in the implementation of regional autonomy and the level of independent. This study uses secondary data by taking locations in the Buton Utara district of west by using the calculation data of the regional revenue and expenditure budget (APBD) for the regency for the period 2015-2018. The analytical method used is quantitative descriptive analysis method which is then analyzed using growth ratio, independence ratio and contribution ratio. The results of the descriptive analysis generally show that is unable to process local revenue (PAD) which causes the independence to be very low. For the reason, it is hoped that the regency government will further improve the managent of regional revenues so that the growth of PAD sources continues to increase.